2009
DOI: 10.1021/bi9005094
|View full text |Cite
|
Sign up to set email alerts
|

Ribonuclease Inhibitor Regulates Neovascularization by Human Angiogenin

Abstract: Human angiogenin (ANG) is a homologue of bovine pancreatic ribonuclease (RNase A) that induces neovascularization. ANG is the only human angiogenic factor that possesses ribonucleolytic activity.To stimulate blood-vessel growth, ANG must be transported to the nucleus and must retain its catalytic activity. Like other mammalian homologues of RNase A, ANG forms a femtomolar complex with the cytosolic ribonuclease inhibitor protein (RI). To determine whether RI affects ANG-induced angiogenesis, we created G85R/G8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 30 publications
3
41
0
3
Order By: Relevance
“…RNH1 affinity for ribonucleases is the key determinant factor for RNase cytotoxicity; only ribonucleases that evade RNH1 can kill a cell. RNH1 also binds to angiogenin (ANG), suggesting a possible role in neovascularization (11), but the extent to which RNH1 may regulate angiogenesis remains unclear. Further, RNH1 contains numerous cysteine residues (e.g., 32 in human RNH1), whose sulfhydryl groups might play key structural roles and protect from oxidative damage (7,12).…”
Section: Introductionmentioning
confidence: 99%
“…RNH1 affinity for ribonucleases is the key determinant factor for RNase cytotoxicity; only ribonucleases that evade RNH1 can kill a cell. RNH1 also binds to angiogenin (ANG), suggesting a possible role in neovascularization (11), but the extent to which RNH1 may regulate angiogenesis remains unclear. Further, RNH1 contains numerous cysteine residues (e.g., 32 in human RNH1), whose sulfhydryl groups might play key structural roles and protect from oxidative damage (7,12).…”
Section: Introductionmentioning
confidence: 99%
“…This would also allow the formation of tiRNA and would therefore shut down protein synthesis. The Ang G85R/G86R variant was shown to have a 10 6 -fold lower affinity for RNH1 than the wild-type enzyme [178]. Further analysis showed that this variant was 10-25 times more cytotoxic than the wild-type enzyme towards the human promyelocytic leukemia cell line HL-60 when fused to H22(scFv) [242].…”
Section: Reducing the Susceptibility Of Angiogenin To Inhibitionmentioning
confidence: 98%
“…It specifically targets smooth muscle cells, endothelial cells and motor neurons, stimulating proliferation, cell migration and tubular development in response to environmental conditions [176,177]. The expression of angiogenin is upregulated in several types of cancer and it promotes the establishment, growth and metastasis of tumors [178,179].…”
Section: Human Angiogeninmentioning
confidence: 99%
See 1 more Smart Citation
“…Ангиогенин стимулирует васкуляризацию тканей: связыва-ясь с актином на поверхнос ти эндотелиальных клеток, ангиогенин претерпевает эндоцитоз, перемещается в ядро, где активирует экспрессию соответствующих генов [34]. Проангиогенная ак-тивность белка зависит от концентрации ионов меди, которые связываются с доменом взаимо-действия с эндотелиальными клетками [35] и модулируют сродство ангиогенина к эндотели-альным клеткам.…”
Section: участие меди в метаболизме стunclassified